Antimicrobial Susceptibility Pattern of Streptococcus pneumoniae among Healthy Carrier Children under Five Years Old attended at Outpatient Department of Largest Teaching Hospital in Bangladesh - Shormin, Moonmoon; Shamsuzzaman, SM; Afroz, Samira; Rashed, Asif (Bangladesh Journal of Infectious Diseases, 2022)
Background: Over the past several decades, antimicrobial resistance in Streptococcus pneumoniae has dramatically increased worldwide. Objectives: The purpose of the present study was to detect and monitor the antibiotic susceptibility pattern of Streptococcus pneumoniae among under five years old children as carrier. Methodology: The cross-sectional study was conducted in the Department of Microbiology of Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh from July 2016 to June 2017 Data were collected among 200 under five children from Pediatric OPD of Dhaka Medical College Hospital. Streptococcus pneumoniae were isolated and identified by culture, Gram staining and biochemical test. Antimicrobial susceptibility test for S. pneumoniae was performed by disc-diffusion method. Results: Out of 200 nasopharyngeal swabs, 67(33.50%) isolates were positive by culture. Among 67 isolated Streptococcus pneumoniae, all the isolates were susceptible to penicillins, cephalosporins, glycopeptides and carbapenems. Among the isolated Streptococcus pneumoniae, 92.53% isolates were susceptible to ciprofloxacin, 52.16% isolates were susceptible to erythromycin and azithromycin. Streptococcus pneumoniae showed very low susceptibility to gentamicin (11.94%) and co-trimoxazole (23.88%). Conclusion: This study has shown the antimicrobial susceptibility pattern of Streptococcus pneumoniae in children as carriers. Bangladesh Journal of Infectious Diseases June 2021;8(1):12-17